The effectiveness of enrichment triad model to enhance students' learning outcomes of history learning. (March 2019) - Sumardi; Surya, R A; Naim, M
Abstract: The requirement of the 21st century proposes many innovation of several facets. Education as a mean of changes plays important role in developing a nation. Meanwhile, there are several issues found which promotes education quality becomes decrease. In order to improve education quality is strengthening educational research. Educational research is a concrete attempt to resolve and develop education practices and provides expected human resources. Many research tried to examine new methods, strategies, techniques within education practice in order to meet learning goals. This article focuses on a new method designed by Joseph Renzulli named Enrichment Triad Model to deal with educational issues found nowadays in the classroom, particularly history learning. Enrichment is a learning method applied to enrich many aspects within learning process. This study is quasi-expermental design. The results based on independent t-test show that Enrichment Triad Model significantly enhaces students' history learning outcomes.